2016
DOI: 10.1007/s13555-016-0160-3
|View full text |Cite
|
Sign up to set email alerts
|

Skin Manifestations of Insulin Resistance: From a Biochemical Stance to a Clinical Diagnosis and Management

Abstract: Worldwide, more than 1.9 billion adults are overweight, and around 600 million people suffer from obesity. Similarly, ~382 million individuals live with diabetes, and 40–50% of the global population is labeled at “high risk” (i.e., prediabetes). The impact of these two chronic conditions relies not only on the burden of illnesses per se (i.e., associated increased morbidity and mortality), but also on their increased cost, burden of treatment, and decreased health-related quality of life. For this review a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 73 publications
1
40
0
12
Order By: Relevance
“…Insulin resistance, the key defect linking obesity and type 2 diabetes [4], also drives increased vascular risk [5]. However precise measurement of insulin resistance in routine clinical practice is usually not feasible [6]. Cutaneous markers of insulin resistance include acanthosis nigricans, androgenetic alopecia, acne, hirsutism and skin tags (acrochordons) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Insulin resistance, the key defect linking obesity and type 2 diabetes [4], also drives increased vascular risk [5]. However precise measurement of insulin resistance in routine clinical practice is usually not feasible [6]. Cutaneous markers of insulin resistance include acanthosis nigricans, androgenetic alopecia, acne, hirsutism and skin tags (acrochordons) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However precise measurement of insulin resistance in routine clinical practice is usually not feasible [6]. Cutaneous markers of insulin resistance include acanthosis nigricans, androgenetic alopecia, acne, hirsutism and skin tags (acrochordons) [6][7][8]. These benign, pedunculated papular lesions are commonly located on the neck, axillae, eyelids and groin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies reported that sebocyte as well as adipocyte share the expression of some adipogenic factors as galectin‐12, resistin, stearoyl‐CoA desaturase (SCD), sterol response element binding protein‐1 (SREBP‐1), and the CCAAT enhancer binding protein α (C/EBPα) during their differentiation . Insulin resistance, the reduced responsiveness of target cells to insulin, has a wide range of skin manifestations such as acrochordons, acanthosis nigricans, androgenetic alopecia, acne, and hirsutism . Irisin is a novel adipomyokine, secreted mainly by adipose tissue and muscles after cleavage of fibronectin type III domain‐containing protein 5 (FNDC5) in response to stimuli such as exposure to cold and physical exercise thus it called the “exercise hormone.” It has been found to be associated with anthropometric and biochemical parameters, other hormones and adipokines, obesity, insulin resistance, type 2 diabetes mellitus, and metabolic syndrome .…”
Section: Introductionmentioning
confidence: 99%
“…Our research centers on the role of insulin and the IR in skin. Diabetes-associated skin pathologies are well documented (15)(16)(17)(18), including severely impaired wound healing leading to amputations and an increased risk of nonmelanoma skin cancer (6,19,20). However, the role of insulin and the IR in the development of these pathologies ABBREVIATIONS: DDW, double-distilled water; EM, electron microscopy; IF, intermediate filament; IR, insulin receptor; KKO, keratin II knockout keratinoctye; PCNA, proliferating cell nuclear antigen; SIRKO, epidermal skin-specific insulin receptor knockout mouse; WT, wild type is not appreciated by most physicians and researchers.…”
mentioning
confidence: 99%